Real convergence in central, eastern and south-eastern Europe - Piotr Żuk; Li Savelin (European Central Bank (ECB), 2018)
This paper analyses real income convergence in central, eastern and south-eastern Europe (CESEE) to the most advanced EU economies between 2000 and 2016. The relevance of this topic stems both from the far-reaching implications of real income convergence for economic welfare and the importance of convergence for economic and monetary integration with, and within the European Union. The paper establishes stylised facts of convergence, analyses the drivers of economic growth and identifies factors that might explain the differences between fast- and slow-converging economies in the region. The results show that the most successful CESEE economies in terms of the pace of convergence share common characteristics such as, inter alia, a strong improvement in institutional quality and human capital, more outward-oriented economic policies, favourable demographic developments and the quick reallocation of labour from agriculture into other sectors. Looking ahead, accelerating and sustaining convergence in the region will require further efforts to enhance institutional quality and innovation, reinvigorate investment, and address the adverse impact of population ageing.
Keywords: E01; F15; O11; O43; O47; O52; O57; 330; Real convergence; economic growth; middle-income trap; EU accession; central; eastern and south-eastern Europe; Western Balkans